Meaning and value of humor in the lives of elderly Malays in Putrajaya, Malaysia - Raja Mohd Khalid, Raja Kamariah (2013)
Humor is universal in nature but does vary across culture. Even though there is growing interest in the study of humor across culture, humor use among elderly Malays in Malaysia is not well understood. The study was to explore the use of humor among elderly Malays living with children in Putrajaya. The purpose of this study was to explore in depth on the meaning and lived experience of humor for elderly Malays, living with their children in Putrajaya. This qualitative research, underpinned by interpretive phenomenological approach, used in-depth semi structured interviews with ten elderly Malays in Putrajaya. Each interview lasted approximately two hours for the first session, followed that, another session was carried out for about one hour to ensure the accuracy of the findings. Each session was transcribed verbatim and analyzed manually. Tesch’s method was used in data analysis in order to obtain common themes for categorization, re-categorization and context processes. Three themes emerged pertinent to the research questions; experience of humor, reasons for using humor and meaning of humor. Humor experience created positive relationship and connection in inter-generational gap between grandparents and grandchildren. In addition to that, the respondents benefited humor for general health improvement, physically, psychosocially and spiritually. The study also found that the meanings given to humor are as verbal outcome of laughter,production humorous anecdotes (jokes) and happiness. The analysis revealed that humor increases self-worth which leads to positive well-being for the elderly even though there are limitations in the use of humor. The results can be regarded as groundwork in understanding the use of humor among elderly Malays. The findings discover few models to improve the well-being of the elderly by using humor as a strategy. Specific plans and programs related to the use of humor are developed to help the elderly to experience positive outcomes of aging.